Associations of Sustainable Development Goals Accelerators With Adolescents’ Well-Being According to Head-of-Household’s Disability Status–A Cross-Sectional Study From Zambia - Chipanta, David; Estill, Janne; Stöckl, Heidi; Hertzog, Lucas; Toska, Elona; Chanda, Patrick; Mwanza, Jason; Kaila, Kelly; Matome, Chisangu; Tembo, Gelson; Keiser, Olivia; Cluver, Lucie (International Journal of Public Health, 2022)
Objective: Examined associations between accelerators (interventions impacting ≥2 SDG targets) and well-being indicators among adolescents 16-24 years old in Zambia. Methods: Surveyed adults 16 years+ from 1,800 randomly sampled households receiving social cash transfers. Using multivariate logistic regressions, examined associations between accelerators (social cash transfers, life-long learning, mobile phone access and seven SDG-aligned well-being indicators among adolescents. Results: Sample comprised 1,725 adolescents, 881(51.1%) girls. Mobile phone access was associated with no poverty (adjusted Odds Ratio [aOR] 2.08, p<0.001), informal cash transfers (aOR 1.82, p=0.004), seeking mental health support (aOR 1.61, p=0.020). Social cash transfers were associated with no disability-related health restrictions (aOR 2.56, p=0.004) and lesser odds of seeking mental health support (aOR 0.53, p=0.029). Life-long learning was associated with informal cash transfers (aOR 3.49, p<0.001) and lower school enrollment (aOR 0.70, p=0.004). Adolescents with disabled head-of-household reported worse poverty, good health, but less suicidal ideation. Conclusions: Social cash transfers, life-long learning, and mobile phone access accelerators were positively associated with SDG aligned well-being indicators. Adolescents living with disabled head-of-household benefited less. Policies should be adapted to correct disability-related inequalities.